2014
DOI: 10.1002/2013jc008899
|View full text |Cite
|
Sign up to set email alerts
|

Observations of flow variability through the Kerama Gap between the East China Sea and the Northwestern Pacific

Abstract: The Kerama Gap, near the middle of the Ryukyu Island chain, is the deepest channel with a sill depth of 1050 m connecting the East China Sea (ECS) to the Northwestern Pacific. We measured the flow through the Kerama Gap from June 2009 to June 2011. The 2 year mean transport, 2.0 6 0.7 Sv, is into the ECS from the Northwestern Pacific; it contributes about 11% of the mean Kuroshio transport in the ECS at the PN line. Subtidal standard deviation of the transport through the Kerama Gap is 3.2 Sv, comparable to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
4
27
1
Order By: Relevance
“…Rather, the observations suggest that indirect eddy effects drive the transport variability at the PN Line, possibly via eddyinduced "streamers" that flow around the islands due to conservation of circulation (Andres and Cenedese, 2013 in the eddy (cyclonic or anti cyclonic), these streamers add to or subtract from the net Kuroshio transport at the PN Line. This idea of eddy-induced flow through the island chain is also consistent with strong flow variability observed in the Kerama Gap in data from an array of CPIESs and current meter moorings (Na et al, 2014) that show transport variability through the gap correlates with the presence of cyclones and anticyclones in the Philippine Basin adjacent to the islands just southwest of the Kerama Gap. In contrast to the western Philippine Basin, transport variability observed at the PN Line (with CPIESs) is well correlated with transport variability in the Kuroshio where it exits the East China Sea through Tokara Strait (from eight hydrographic sections; Nakamura et al ) is consistent with the speeds of the velocity cores in the mean cross section here (Figure 3c).…”
supporting
confidence: 80%
“…Rather, the observations suggest that indirect eddy effects drive the transport variability at the PN Line, possibly via eddyinduced "streamers" that flow around the islands due to conservation of circulation (Andres and Cenedese, 2013 in the eddy (cyclonic or anti cyclonic), these streamers add to or subtract from the net Kuroshio transport at the PN Line. This idea of eddy-induced flow through the island chain is also consistent with strong flow variability observed in the Kerama Gap in data from an array of CPIESs and current meter moorings (Na et al, 2014) that show transport variability through the gap correlates with the presence of cyclones and anticyclones in the Philippine Basin adjacent to the islands just southwest of the Kerama Gap. In contrast to the western Philippine Basin, transport variability observed at the PN Line (with CPIESs) is well correlated with transport variability in the Kuroshio where it exits the East China Sea through Tokara Strait (from eight hydrographic sections; Nakamura et al ) is consistent with the speeds of the velocity cores in the mean cross section here (Figure 3c).…”
supporting
confidence: 80%
“…Through strait northeast of Taiwan and the Kerama gap, they influence the spatio-temporal structure of the Kuroshio in the ECS (Zhang et al, 2001;Na et al, 2014). With this effect, the Kuroshio volume transport (KVT) may exhibit significant intraseasonal variability as demonstrated by Andres et al (2008) using continuous 13-month in-situ observation at the PN Section ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[] and Na et al . [] revealed that the temporal variability of transport through the Kerama Gap, located just south of these four channels, is related to the arrival of mesoscale eddies propagating from the east. In their studies, the mesoscale eddy is assumed to be surface intensified.…”
Section: Residual Currentsmentioning
confidence: 99%
“…The Kerama Gap south of Okinawa is the most well‐known and deepest channel, with a sill depth of 1050 m, and connects the ECS with the surrounding ocean. Previous studies have investigated the impact of water exchanges via the Kerama Gap on the interaction between the Kuroshio and the Ryukyu Current [ Nitani , ; Morinaga et al ., ; Andres et al ., ; Nakamura et al ., ; Na et al ., ; Yu et al ., ; Nishina et al ., ]. Andres et al .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation